Taphonomy of Small Predators multi-taxa accumulations: palaeoecological implications. (18th August 2018) - Denys, C.; Stoetzel, E.; Andrews, P.; Bailon, S.; Rihane, A.; Huchet, J. B.; Fernandez-Jalvo, Y.; Laroulandie, V.
Abstract: Most small terrestrial vertebrate accumulations in archaeological and palaeontological sites result from predation but we are far from having an exhaustive knowledge of modern predators' diet, ecological niches and bone modification patterns especially in North African sites. The few neotaphonomic referentials available result from taxon-specialized palaeontologists' initiatives. A survey of the literature on North Africa predators shows that their prey diversity is high and not only include rodent and shrews but also amphibians, squamates, bats and insects. We performed here a pilot taphonomic study of a Moroccan Tyto alba nest pellets including the whole taxa consumed (birds, rodents, shrews, amphibians, insects). We analyzed bone representation, fragmentation and digestion for each taxa and then compared the results. We observe differences between the taxa but on the whole find higher modification levels for this assemblage compared to roost sites of barn owls from other sites. We used for the comparisons homologous bones like the femur and the humerus and also found differences between the taxa. For example, digestion was lower on amphibians and birds than on micromammals. We discuss here some methodological issues as well as archaeological and palaeoenviromental ones by comparison with the Pleisto-Holocene site of El Harhoura II (Morocco).